Trade Persistence and the Limits of Trade Agreements - Florian Moelders (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2011)
International trade ows reveal strong persistence over time. This paper is concerned with the role of trade agreements in this persistent environment. The data reveal a high level of heterogeneity of the trade- creating effect along the trade volume and per-capita income distributions. If controlled for persistence in bilateral trade ows, I find that higher per- capita incomes are associated with smaller increases in bilateral trade ows if an agreement is present, compared to lower-income countries. This gives rise to a re-assessment of trade agreements and hence of economic policy. While they are a powerful tool for trading partners at the lower end of the per-capita income distribution, they are less so at the upper end.
Keywords: F10; F13; F15; 330; Trade agreements; Gravity model; Trade persistence